Några finska kyrkogravar med pärlor från 1600-1700-talen - Hiekkanen, Markus (Hikuin, 2006)
Church graves with beads from 17th and 18th centuries in Finland By Markus Hiekkanen Very few studies concerning artefacts found in graves during post-medieval time in Finland have been carried out. This article presents a group of graves excavated in Finnish medieval stone churches which have the common feature that necklaces have been found in them. The beads most often are of glass while a minority are of e.g. gagat, amber, horn and other materials. No typological or stylistic study concerning the beads has been carried out for this article (Anna Väänänen, University of Turku, has currently finished her Mag. Phil. thesis e.g. along these lines). Only in few cases the archaeological investigation can have been carried out in such detail that the necklaces definitely can be said to have been around the neck of the deceased. Still, in many cases clusters of beads in a restricted area strongly point to this. The number of certain or almost certain necklaces is ca 15. The find circumstances and historical data give together as a result that graves with beads appear not earlier than the middle of the 17th century and that they disappear during after the middle of the 18th century. It seems that necklaces were only carried in graves by women. The distribution of the graves inside a church seems to show that they are more often to be found on the northern than on the southern side of the central east-west axis of the nave. The reason for burying the dead with necklaces is not easy to find. One possibility could be that the catholic tradition of rosary still was alive in parts of Finland during the late 17th century. In fact, there is historical knowledge towards this at least during the first half of the century. Still, the necklaces are found around the neck of the deceased, not around their wrists which would be a proper way to carry a rosary. According to the author the most probable reason to bury dead between around 1650 and 1780 AD with a necklace was to adapt to the custom of the upper classes of the society with their habit of wearing necklaces. – A catalogue (attached to the end of the article) of beads found in archaeological excavations of Finnish medieval stone churches in the end of the article contains documentation of approximately 1000 beads from 39 churches.